The Body in Christianity on the Basis of the Crisis of the Corporeal in Modern Culture (Laisvalaikio tyrimai, 2023)
Relevance of the topic. The article is devoted to the meanings and practises of the body in Christian culture and the issue of preserving and continuing this tradition in contemporary culture. Since it is about the semantic contexts of the body, the article uses the phenomenological method in combination with hermeneutic analysis.The authors consistently deploy several logical lines. The first line is related to the description of such a direction as hesychasm, its practises and attitude to the body. At the same time, the ethical potential of hesychasm and the pathos of physicality as an instrument of morality are emphasised. The second line revolves around the practical attitude to the body in modern culture: the preservation of the Christian tradition, the natural characteristics of the body, and understanding the meaning of the body. The third line is connected with the loss of the “sanctity” of the body and the unawareness of this loss on the part of the common citizen and, as a result, the erosion of the ethical and natural meaning of the body. According to the authors, history will show how terrible these changes in meaning can be. The “distortion” of the meaning of the body in modern cultures makes it possible to emphasise the emergence of the phenomenon of unconsciousness of paradoxical events, the enormity of the consequences of which few people still understand. The problem. Today, the events that unfold around the topic of the corporeal directly and indirectly touch on the topic of human relations and, as a result, there is a need to once again talk about the role and significance of the body in the Christian tradition and about the consequences of ignoring the biblical commandments in modern everyday life. The purpose. To clarify the meanings of the corporeal, based on the tradition of hesychasm.Research object. The role and significance of the body in the Christian tradition and about the consequences of ignoring the biblical commandments in modern everyday life.Results. In the article, it was shown that the body and its meaning have a special ethical pathos because its understanding was formed under the enormous influence of Christianity, which laid the foundations for the formation of the context of the general civilisational development of mankind. Modern culture “distorts” the meaning of the body, and the actual material of sports competitions makes it possible to record the phenomenon of unawareness in most people that there is a departure from universal values (this is what is called a crisis of culture). History moves in such a way that sometimes it is impossible to trace the trajectories of its development. And yet, despite the incomprehensible lines of development, does the question of the relationship with the Absolute remain relevant for a man? If the Christian meanings of the body fade into the background of life, then what other religion will be able to promote the ideas of ethics and morality?Keywords. Hesychasm, Christian tradition, meanings of the body, transgender, sports competitions, the pathos of the body, contemporary culture.